A master class on being human : a Black Christian and a Black secular humanist on religion, race, and justice - Braxton, Brad Ronnell; Pinn, Anthony B. (Beacon Press, 2023)
"A conversation between 2 eminent Black thinkers on how to work together to make the world a better place despite deep religious differences"--